The role of Tet2 and Tet3 in the molecular programming of blood cell differentiation during zebrafish development - Alayed, Amal Saeed M (2025)
DNA methylation is an epigenetic mark that regulates gene expression during cellular differentiation. Ten-eleven translocation (Tet) dioxygenase enzymes are involved in active demethylation and are required for hematopoietic stem cell (HSC) differentiation. HSCs arise from haemogenic endothelial cells (HECs) in arterial vessels, which depend on Notch signalling for their specification. Initially, the loss of HSC formation in tet2/tet3 double mutants was attributed to a failure in HEC formation caused by defective Notch signalling, despite normal vascular patterning and arterial specification. This study aimed to reinvestigate Notch signalling and HEC development in the ventral wall of the dorsal aorta (vDA) of tet2/tet3 double mutants to resolve these inconsistencies. Here, the Notch reporter transgene csl:mCherry was expressed in the endothelium of the vDA in the absence of Tet2 and Tet3. Confocal analysis of the gene trap line qmc551, which exhibits GFP expression in primitive red blood cells (prRBCs) and HECs of the vDA, demonstrated normal GFP expression in HECs of the vDA at 2 days post fertilisation (dpf). It also revealed a few GFP+ hematopoietic stem and progenitor cells (HSPCs) in the mesenchyme below the DA in tet2/tet3 double mutants. Whole-mount in situ hybridisation (WISH) experiments using the HEC marker growth factor independence 1aa (gfi1aa) revealed that, at 40 hours post fertilisation (hpf), gfi1aa expression persisted in the HECs of the vDA in tet2/tet3 double mutant embryos, contrasting with its typical downregulation in wild-type (WT) embryos at this stage. These findings suggest a defect in the endothelialto- hematopoietic transition (EHT), likely resulting from disrupted epigenetic programming of HECs in the absence of the two Tet proteins. In tet2/tet3 double mutant embryos, circulation appeared normal without evident shunts; however, blood flow velocity was reduced. To investigate the molecular programming underlying these defects, single-cell transcriptome analysis was performed on a cell population enriched for qmc551:GFP and Gata1a:dsRed single and doublepositive cells isolated from 2dpf WT and tet2/tet3 double mutant embryos. Transcriptomic analyses revealed significant downregulation of key endothelial genes, such as apelin, plvapb, casz1, and pecam1. These data suggest a critical role for Tet2 and Tet3 in endothelial programming and angiogenesis. The analysis also showed significant downregulation of erythroid genes in prRBCs. WISH experiments revealed increased gata1a expression in circulating prRBCs at 2 and 3dpf, indicating a late maturation defect in tet2/tet3 double mutant embryos. Additionally, reduced slc4a1a mRNA expression in mutants at 20hpf, prior to the onset of circulation, suggests delayed early differentiation of prRBCs. These findings indicate that the absence of both Tet2 and Tet3 leads to delayed erythroid development. In summary, this study elucidates the multifaceted roles of Tet2 and Tet3 proteins in regulating both primitive and definitive hematopoietic waves during zebrafish embryogenesis.